(untitled) (Journal of history, 2020)
This article analyzes the discussion of views and opinions about the domestication of the horse and the ancient botays and terseks. Once the 40 years of the twentieth century terseks antiquities, after having opened the botai culture of ancient horse-breeders, the territory of Kazakhstan has been regarded as one of the domestication of horses regions. This state- ment meets a rich osteological material from the sites above mentioned crops. But, despite that in science there are conflicting views. If one group of scientists fully approves of domestication and botays and terseks horses, another group disagreed with this opinion. The author shows the position of domestic and foreign scientists, conducts scientific analysis of these pa- pers researchers voiced the problem. The article also preprinyata attempt to define the role and botays and terseks monuments in the ancient history of Kazakhstan.